Fetal brain injury in complicated monochorionic pregnancies: diagnostic yield of prenatal MRI following surveillance ultrasound and influence on prognostic counselling†. (23rd May 2017) - Robinson, Alice; Teoh, Mark; Edwards, Andrew; Fahey, Michael; Goergen, Stacy
Abstract: Objective: This study aimed to determine the additional diagnostic information provided by prenatal (fetal) magnetic resonance imaging (pMRI) following tertiary ultrasound (US) for fetal cranial abnormalities in complicated monochorionic gestations. Methods: Women with complicated monochorionic gestations complicated by twin–twin transfusion syndrome, co‐twin demise (CD), selective intrauterine growth restriction, and/or twin anaemia–polycythaemia sequence who were referred for pMRI after tertiary US were included. Additional diagnostic information by pMRI that changed prognostic counselling was the primary outcome. Results: Thirty‐three women with 48 live fetuses had pMRI at a median of 25 weeks (range: 21–29). Three of ten survivors of spontaneous CD, one of eight survivors of CD after twin–twin transfusion syndrome and 1/30 co‐survivors had diagnostic information added by pMRI that altered counselling; US was normal in two and in the other three underrepresented parenchymal injury (5/33 = 15%; 95% confidence interval ±0.27–0.03). Additional findings included occipital lobe infarction, hemispheric injury, dural sinus thrombosis, ischaemia‐producing polymicrogyria and intraventricular haemorrhage. Another 8/33 women had additional information provided by pMRI that did not alter counselling. Conclusion: Prenatal magnetic resonance imaging resulted in changed prognostic counselling in 5/33 pregnancies. Evaluation of incorporation of pMRI into routine surveillance of complicated monochorionic gestations is needed. © 2017 John Wiley & Sons, Ltd. Abstract : What is already known about this topic: Complicated monochorionic pregnancies are associated with an increased risk of adverse neurodevelopmental outcome with some injuries occurring prenatally, and prematurity is likely to be a significant contributing factor to these adverse outcomes. A small number of case series have reported increased sensitivity and specificity of magnetic resonance imaging (MRI) compared with ultrasound for fetal brain injuries following twin–twin transfusion syndrome (TTTS) and co‐twin demise. What does this study add: Fetuses with normal cranial ultrasound who were survivors of co‐twin demise either before or after TTTS were more likely to have abnormal brain MRI findings that changed prognostic counselling than were co‐survivors of TTTS, selective intrauterine growth restriction, or twin anaemia–polycythaemia sequence. Addition of fetal MRI to the routine surveillance of complicated monochorionic gestations (cMCGs) with ultrasound may help to refine neurodevelopmental prognostication, and therefore pregnancy management, and post‐natal care of children who are survivors of co‐twin demise. A prospective evaluation of the incorporation of fetal MRI, including brain volumetry, into the routine surveillance of cMCGs is required to inform clinical practice guidelines regarding the routine use of MRI in the imaging surveillance of these pregnancies.